Simulating a Post-Fordist urban system: Results from the PF.US model - Sylvie Occelli; Giovanni A. Rabino (European Regional Science Association (ERSA), 1998)
In a previous we argued that some major novelties to be addressed by a new generation of urban models should be related to: i) the knowledge expectations connected with the use of a model (i.e. epistemological background), ii) the feasibility of its application domain (i..e. the operational underpinnings) and iii) the urban phenomena and perceptions characterizing the present cities ( i.e. the so-called Post-Fordist cities). We also emphasized that many drawbacks and limitations which nowadays make the classical urban modelling unsatisfactory were not caused so much by their methodological underpinnings but rather by the limited scope of the whole model application. This paper presents an operational simulation model (the PFUS model) which broadens the focus of the classical model application and allows to explore some features of the new kind of development taking place in modern cities (i.e. the local-global interactions, the role of localized resources). The paper is articulated into three parts. Part 1 outlines the conceptual and formalised structure of the model. Part 2 presents the results of its application to the Piedmont region. Finally in part 3 the main novelties of the PFUS model application are discussed emphasizing in particular their implicattions for planning purposes.
Keywords: 330